2016
DOI: 10.2147/ppa.s117774
|View full text |Cite
|
Sign up to set email alerts
|

Examining patient preferences in the treatment of rheumatoid arthritis using a discrete-choice approach

Abstract: BackgroundBiological disease-modifying antirheumatic drugs (bDMARDs) used in second-line treatment of rheumatoid arthritis (RA) are administered parenterally. However, so-called targeted synthetic DMARDs (tsDMARDs) – developed more recently – offer alternative (ie, oral) administration forms in second-line treatment. Since bDMARDs and tsDMARDs can be regarded as equal in terms of efficacy, the present study examines whether such characteristics as route of administration drive RA patients’ treatment choice. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 39 publications
10
70
2
6
Order By: Relevance
“…Results from the previous literature on patient and physician preferences for biologic therapy suggest a disconnect in patient and physician perceptions . Results of the 2 surveys reported here, along with the results of previous patient preference studies may address this disconnect by providing physicians with information regarding patients’ attitudes and concerns around different rheumatology treatments. This understanding of the patient perspective may help guide physicians’ discussions with their patients about different biologic therapy options.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Results from the previous literature on patient and physician preferences for biologic therapy suggest a disconnect in patient and physician perceptions . Results of the 2 surveys reported here, along with the results of previous patient preference studies may address this disconnect by providing physicians with information regarding patients’ attitudes and concerns around different rheumatology treatments. This understanding of the patient perspective may help guide physicians’ discussions with their patients about different biologic therapy options.…”
Section: Discussionmentioning
confidence: 59%
“…For RA patients with active disease despite conventional DMARDs, current recommendations do not specify a treatment of choice from among approved anti–tumor necrosis factor (anti‐TNF) inhibitors (e.g., adalimumab, certolizumab pegol, etanercept, golimumab, or infliximab) or the non‐TNF options (e.g., abatacept, anakinra, rituximab, sarilumab, tocilizumab, and tofacitinib) in some cases . The choice of biologic therapy for each patient is generally based on consideration of patient‐related factors, disease‐related factors, the mechanism of action of the prescribed medication, and patient preferences for treatment .
A general preference for subcutaneous biologic therapies has previously been reported among rheumatology patients. Results of the current surveys indicate that rheumatoid arthritis patients, including biologic‐naive patients, are generally open to intravenous or subcutaneous treatment. Patients receiving intravenous therapy express high satisfaction with this route of administration.
…”
Section: Introductionmentioning
confidence: 99%
“…In that study, however, short infusions (30-60 min) and long infusions (2-3 h) were preferred a little more and a little less, respectively, to the oral mode of administration. Alten et al 47 found that among patients with rheumatoid arthritis, oral tablets were significantly preferred to both IV infusions and SC injections. In the two studies, however, the mode of administration and frequency of administration were not combined, which might explain the differences in preference across the studies.…”
Section: Discussionmentioning
confidence: 99%
“…In another US survey of 250 RA patients who had discontinued anti-TNF therapy, 41% cited injection experience (pain/burning/discomfort during or after injection, redness/swelling after injection, dislike of self-injection or of injection frequency, fear of needles) as an important reason for discontinuation 10. A German discrete-choice experiment performed in 1,588 RA patients found that “oral administration” and “no combination with methotrexate” were the most highly desired characteristics of a second-line DMARD, with “intravenous infusion” being among the most strongly rejected 11. The authors concluded that an oral DMARD excluding methotrexate is a highly favorable treatment option that may increase compliance and adherence in RA treatment.…”
Section: Discussionmentioning
confidence: 99%